Analisis Akad Jual-beli Kain Gulungan dalam Penggunaan Hak Khiyar Menurut Fikih Muamalah - Indriyani; Muhammad Yunus (Jurnal Riset Ekonomi Syariah, 2021)
Abstract. This thesis uses the results of (field research) related to "Analysis of the Sale and Purchase Agreement of Rolled Fabrics in the Use of Khiyar Rights According to Fiqh Muamalah (Case Study at Z Market)".This thesis research aims: (1) To find out the concept of khiyar in buying and selling according to muamalah fiqh (2) To find out the practice of khiyar in buying and selling rolled cloth at the Z market (3) To find out an overview of fiqh muamalah the practice of khiyar in buying and selling rolled cloth at Z Market. The method used in this study is a qualitative research method in the field of normative law, namely examining the arguments of the Qur'an and Hadith as well as the opinions of scholars related to khiyar rights in the contract of buying and selling cloth rolls at the Z Market based on primary and secondary data. secondary data obtained from the field. The results of this study indicate that the use of khiyar rights in the sale and purchase of rolled cloth at the Z Market fulfills the pillars and conditions of sale and purchase. Merchants apply a bargaining system and allow the exchange of goods if the discrepancy meets the conditions agreed upon by the seller and the buyer. However, in buying and selling, the seller should guarantee the buyer to khiyar so as not to feel disadvantaged. The sale and purchase transaction between the parties should do justice by bearing the profits and losses so that the benefit in buying and selling can be achieved. Abstrak. Skripsi ini menggunakan hasil penelitian lapangan (field research) berkaitan dengan “Analisis Akad Jual-beli Kain Gulungan Dalam Penggunaan Hak Khiyar Menurut Fikih Muamalah (Studi Kasus di Pasar Z)”. Penelitian skripsi ini bertujuan: (1) Untuk mengetahui konsep khiyar dalam jual-beli menurut fikih muamalah (2) Untuk mengetahui praktik khiyar dalam jual-beli kain gulungan di pasar Z (3) Untuk mengetahui tinjauan fikih muamalah praktik khiyar dalam jual-beli kain gulungan di Pasar Z. Metode yang digunakan penelitian ini adalah metode penelitian kualitatif dalam bidang ilmu hukum normatif, yaitu mengkaji dalil-dalil al-Qur’an dan Hadits serta pendapat ulama yang terkait hak khiyar dalam akad jual-beli kain gulungan di Pasar Z berdasarkan data primer dan sekunder yang didapatkan dari lapangan. Hasil penelitian ini menunjukkan bahwa penggunaan hak khiyar dalam jual-beli kain gulungan di Pasar Balubr Town Square memenuhi rukun dan syarat jual-beli. Pedagang menerapkan sistem tawar-menawar dan memperbolehkan penukaran barang apabila ketidaksesuaian tersebut memenuhi syarat yang telah disepakati penjual dan pembeli. Namun, dalam melakukan jual-beli hendaknya penjual menjamin pembeli untuk khiyar agar tidak merasa dirugikan. Hendaknya, transaksi jual-beli diantara para pihak melakukan keadilan dengan menangggung keuntungan maupun kerugian agar kemashlahatan dalam jual-beli dapat tercapai.